2010
DOI: 10.1007/s10549-010-1219-y
|View full text |Cite
|
Sign up to set email alerts
|

Biologic role of activated leukocyte cell adhesion molecule overexpression in breast cancer cell lines and clinical tumor tissue

Abstract: The activated leukocyte cell adhesion molecule (ALCAM) is overexpressed in many mammary tumors, but controversial results about its role and prognostic impact in breast cancer have been reported. Therefore, we evaluated the biologic effects of ALCAM expression in two breast cancer cell lines and a larger cohort of mammary carcinomas. By stable transfections, MCF7 cells with ALCAM overexpression and MDA-MB231 cells with reduced ALCAM levels were generated and analyzed in functional assays and cDNA microarrays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…For example, Piao et al (18) found high membranous ALCAM expression to be statistically correlated with a worse clinical course and high cytoplasmic staining with local recurrence. hein et al (17) found high ALCAM expression linked to shorter overall survival compared to patients with low/moderate ALCAM scores, while ALCAM-negative tumors had an intermediate position. Burkhardt et al (15) reported that strong cytoplasmic ALCAM expression was significantly associated with earlier disease progression, while there was no correlation between membranous ALCAM expression and clinicopathological data.…”
Section: Alcam Ihc Results ------------------------------------------mentioning
confidence: 98%
See 4 more Smart Citations
“…For example, Piao et al (18) found high membranous ALCAM expression to be statistically correlated with a worse clinical course and high cytoplasmic staining with local recurrence. hein et al (17) found high ALCAM expression linked to shorter overall survival compared to patients with low/moderate ALCAM scores, while ALCAM-negative tumors had an intermediate position. Burkhardt et al (15) reported that strong cytoplasmic ALCAM expression was significantly associated with earlier disease progression, while there was no correlation between membranous ALCAM expression and clinicopathological data.…”
Section: Alcam Ihc Results ------------------------------------------mentioning
confidence: 98%
“…Burkhardt et al (15), for example, found 75% ALCAM-expressing cancers among 160 analyzed cases. Ihnen et al (27) showed that 95% of their 162 breast cancers were ALCAM-positive, while hein et al (17) demonstrated 79% ALCAM-expressing breast cancers in their cohort comprising 347 cases. Another study analyzing 84 cases found 96% of the tested breast cancers to be ALCAM-positive (28).…”
Section: Alcam Ihc Results ------------------------------------------mentioning
confidence: 99%
See 3 more Smart Citations